Endodontic Management of a Severely Dilacerated Mandibular Third Molar: Case Report and Clinical Considerations - Suraj Arora; Gurdeep Singh Gill; Priyanka Setia; Anshad Mohamed Abdulla; Ganapathy Sivadas; Vaishnavi Vedam (Case Reports in Dentistry)
This article aims at providing an insight to the clinical modifications required for the endodontic management of severely dilacerated mandibular third molar. A 35-year-old patient was referred for the root canal treatment of the mandibular left third molar. An intraoral periapical radiograph revealed a severe curvature in both the canals. A wide trapezoidal access was prepared following the use of intermediate-sized files for apical preparation. Owing to increased flexibility, Hero Shaper NITI files were used for the biomechanical preparation and single cone obturation was carried out. Third molars owing to their most posterior location-limited access coupled with a severe curvature pose utmost clinical challenges require meticulous skill, advanced technology, and patience to achieve success.